Genetic Evidence of a Role for Lck in T-Cell Receptor Function Independent or Downstream of ZAP-70/Syk Protein Tyrosine Kinases - Wong, Jane (American Society for Microbiology, 1998)
T-cell antigen receptor (TCR) engagement results in sequential activation of the Src protein tyrosine kinases (PTKs) Lck and Fyn and the Syk PTKs, ZAP-70 and Syk. While the Src PTKs mediate the phosphorylation of TCR-associated signaling subunits and the phosphorylation and activation of the Syk PTKs, the lack of a constitutively active Syk PTK has prohibited the analysis of Lck function downstream of these initiating signaling events. We describe here the generation of an activated Syk family PTK by substituting the kinase domain of Syk for the homologous region in ZAP-70 (designated as KS for kinase swap). Expression of the KS chimera resulted in its autophosphorylation, the phosphorylation of cellular proteins, the upregulation of T-cell activation markers, and the induction of interleukin-2 gene synthesis in a TCR-independent fashion. The KS chimera and downstream ZAP-70 or Syk substrates, such as SLP-76, were still phosphorylated when expressed in Lck-deficient JCaM1.6 T cells. However, expression of the KS chimera in JCaM1.6 cells failed to rescue downstream signaling events, demonstrating a functional role for Lck beyond the activation of the ZAP-70 and Syk PTKs. These results indicate that downstream TCR signaling pathways may be differentially regulated by ZAP-70 and Lck PTKs and provide a mechanism by which effector functions may be selectively activated in response to TCR stimulation.